Pengaruh Perbandingan Pelarut Ekstraksi Etanol-Air Terhadap Perolehan Kadar Senyawa Fenolat Total Dan Daya Antioksidan Dari Daun Dewa (Gynura pseudochina(L.) DC) - Krisyanella Krisyanella; Andriani Amran; Harrizul Rivai (STIFARM Padang, 2012)
Study about comparative influence of ethanol – water as solvent extraction of phenolic compounds from Dewa leaves (Gynura pseudochina (L) DC ) and it’s antioxidant activity has been done. The solvent ratios tested were 100:0; 80:20; 70:30; 60:40; 50:50. The result showed that the ratio of ethanol – water used as solvent has a significant correlation to an extractable material, phenolic compound and it’s antoxidant activity (P <0.05 ). The best solvent obtained by ethanol – water of 60 : 40, which gave the highest phenolic compound and antioxidant activity.